2015
DOI: 10.4995/eurocall.2015.4665
|View full text |Cite
|
Sign up to set email alerts
|

Facebook for informal language learning: Perspectives from tertiary language students

Abstract: This paper investigates the use of Facebook for out-of-class, informal language learning. 190 New Zealand university language students (Chinese, German, French, Japanese and Spanish) completed an anonymous online questionnaire on (1) their perceptions of Facebook as a multilingual environment, (2) their online writing practices and (3) their views on the educational value of their experiences. Findings indicate that language students are using a range of Facebook features to expose themselves to the languages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 13 publications
4
26
0
2
Order By: Relevance
“…First, Facebook provided an informal environment where there was less pressure to produce language as compared to the language classroom; second, Facebook also provided opportunities to observe native speaker activities and their conversations, providing a space for exposure to authentic language; and third, Facebook provided opportunities to observe and participate in real conversations with native speakers, about interesting topics, using relevant language. Similar to other studies, Alm (2015) discovered that Facebook provided an alternative venue for the students to practice their L2 in an authentic and real setting, providing a more casual and intimate environment where beginner and shy students feel less shy and more confident to interact in the language they are studying.…”
Section: Review Of Literaturesupporting
confidence: 66%
See 3 more Smart Citations
“…First, Facebook provided an informal environment where there was less pressure to produce language as compared to the language classroom; second, Facebook also provided opportunities to observe native speaker activities and their conversations, providing a space for exposure to authentic language; and third, Facebook provided opportunities to observe and participate in real conversations with native speakers, about interesting topics, using relevant language. Similar to other studies, Alm (2015) discovered that Facebook provided an alternative venue for the students to practice their L2 in an authentic and real setting, providing a more casual and intimate environment where beginner and shy students feel less shy and more confident to interact in the language they are studying.…”
Section: Review Of Literaturesupporting
confidence: 66%
“…The large majority used English as the default language. Nevertheless, Alm (2015) found that the more advanced the students are in their language study, the more likely it is for them to keep the language setting to the L2 they were studying or changing the language back and forth between English and their L2. The more advanced students were also more likely to be part of a study group set up by students and to belong to special interest groups.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Tifferet & Vilnai-Yavetz (2014) have supported the findings of present study have discussed that there is a positive and significant gender differences in the context of language features and self-representation. Alm (2015) has revealed that writing experiences on Facebook was perceived to be useful for the formal language writing context, suggesting the need for connecting strategies between formal and informal writing environments.…”
Section: Discussionmentioning
confidence: 99%